(3cJGH aj GdCOYjI hGdRjGQIs - (3eLghds
(3ChdgG (B:s
(3ChdgG(B: (3GdSdGe Ydjc jG JGdj cJGH Gddg hJQLeGfg, GdSdGe Ydjc aj CfGA djdc hCWQGa fgGQc, GdSdGe Ydjc jG HbjI Gddg aj CQVgs
(3BNQgG (B:s
(3BNQgG(B: (3hGQRbfj eQGabI GdCfHjGA aj ebYO UOb YfO edjc ebJOQ, Gddge dc GdMeO Ydi MSf HdGAc hUfYc hdO GdMeO Ydi GdESdGes
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs